The impact of artificial intelligence on international trade in selected Sub-Saharan African countries - Mashao, Teboho Charles; Choga, Ireen (Asian Journal of Economic Modelling, 2025)
The primary objective of this paper was to empirically examine the impact of artificial intelligence on international trade in selected Sub-Saharan African countries for the period 2020 to 2024. The study utilized the Generalized Method of Moments (GMM) estimator to analyze annual panel data. The findings indicate that artificial intelligence has a positive and statistically significant effect on trade flows. This suggests that artificial intelligence influences international trade in Sub-Saharan African countries. Additionally, the results confirm that inflation and gross domestic product (GDP) significantly impact international trade. Overall, artificial intelligence, inflation, and GDP play crucial roles in shaping international trade in Sub-Saharan Africa. The outcomes of this research underscore the important contribution of artificial intelligence to international trade in the region. Consequently, this study advocates for the adoption and utilization of artificial intelligence technology to enhance trade activities. Furthermore, governments should consider revising policies and regulations within the trading sector to facilitate the adoption and utilization of artificial intelligence. Such measures may strengthen global trade governance and promote globalization. When formulating policies related to artificial intelligence, policymakers should also account for other factors affecting international trade, such as GDP and inflation.